Rethinking the oversight conditions of human–animal chimera research. (11th August 2020) - Piotrowska, Monika
Abstract: New discoveries are improving the odds of human cells surviving in host animals, prompting regulatory and funding agencies to issue calls for additional layers of ethical oversight for certain types of human–animal chimeras. Of interest are research proposals involving chimeric animals with humanized brains. But what is motivating the demand for additional oversight? I locate two, not obviously compatible, motivations, each of which provides the justificatory basis for paying special attention to different sets of human–animal chimeras. Surprisingly, the sets of animals that actually get flagged for special scrutiny by research and funding guidelines do not correlate with either of the sets of animals that arise when we think about what is motivating additional oversight. What this shows is that existing research policies and funding guidelines are disconnected from their motivation: the rationale for flagging certain types of human–animal chimeras as requiring special oversight is ignored in execution.